Polskie prawo nieletnich w świetle Reguł Minimalnych Narodów Zjednoczonych dotyczących Wymiaru Sprawiedliwości Nieletnich - Grześkowiak, Alicja (Wydział Prawa i Administracji UAM, 1987)
The VIIth UN Congress on the Prevention fo Delinquency and Procedure with respect to Offenders, held in Milano in September 1985, adopted Minimum Rules of the Administration of Justice towards juveniles (so-called Beijing Rules), subsequently approved by the UN General Assembly on its 40th session in November 1985. Since then they possess the character of guidelines binding on all member- -states. The said rules determine the universal standard model for proceedings in cases of delinquent or socially unadjusted juveniles. The UN General Assembly invited the member states to harmonize their domestic legislation on the administration of justice with respect to juveniles with the Beijing Rules. In the first part of her article, the author presents main solutions adopted in the UN minimum rules, stressing those which possess the character of warranty, i.e. determine the rights of the juveniles and their parents in legal proceedings. The second part of the article confronts the principles established by the Beijing Rules with the Polish law on the juvenile delinquents' cases contained in the Law of October 26, 1982 on proceedings in the juvenile delinquents' cases and in executory acts enacted by virtue on the Law of 1982 as well as in the provisions of the Criminal Code, especially in Art. 8 § 2. The author states that only some of the Polish solutions correspond satisfactorily with the Beijing Rules; in a greater part they do not meet the standard set by the minimum rules. The greatest differences result from the absence in the Polish legislation of the norms regulating the rights of the juveniles and their parents in the legal proceedings. Te above leads to the conclusion that it is necessary to amend the provisions of the Law of 1982 which do not correspond with the Beijing Rules.
Proceedings in juvenille delinquents' Cases in Poland in the light of the un Minimum Rules concerning the Administration of Justice with respect to juveniles